DAKWAH: MISI PENYEBARAN AGAMA DAN TRANSFORMASI SOSIAL - BAGUS PRAYUGO BAGUS (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Abstract. Da'wah is a picture of someone who is conveying da'wah messages in front of a large congregation. Islamic Da'wah is a mission to spread the Islamic religion throughout history. The process of Islamic da'wah shows continuous, continuous and gradual activities. Da'wah activities are calling, inviting and calling people to believe and obey Allah. Da'wah is not only an activity to spread religious teachings, but is also a medium for social transformation in dealing with social problems such as extremism, intolerance, failure to understand the local context and humanitarian problems. The aim of this research is to find out the mission of spreading religion and social transformation. In this research, the author used qualitative methods to analyze descriptively. The data collection method used in this research is literature study, which is supported by theories obtained from journals and books. Social transformation always causes changes in society, one of which is globalization which causes various positive and negative impacts from the positive side, for example the development of science and technology which can be enjoyed by all social groups in society. Through da'wah, people must be encouraged to master science and technology in facing the ever-growing social transformation. Da'wah also motivates the people to work so that economic potential can be directed towards the right path, so that in the end the people can achieve glory. Social transformation that is good and approved by Allah SWT is then the task and responsibility of humans. Keywords: Da'wah, Islam, Social Transformation